Surface Vibration Reconstruction using Inverse Numerical Acoustics - Martinus, F.; Herrin, D. W.; Seybert, A. F. (Journal of Engineering and Technological Sciences, 2003)
This paper explores the use of inverse numerical acoustics to reconstruct the surface vibration of a noise source. Inverse numerical acoustics is mainly used for source identification. This approach uses the measured sound pressure at a set of field points and the Helmholtz integral equation to reconstruct the normal surface velocity. The number of sound pressure measurements is considerably less than the number of surface vibration nodes. An overview of inverse numerical acoustics is presented and compared with other holography techniques such as nearfield acoustical holography and the Helmholtz equation least squares method. In order to obtain an acceptable reproduction of the surface vibration, several critical factors such as the field point selection and the effect of experimental errors have to be handled properly. Other practical considerations such as the use of few measured velocities and regularization techniques will also be presented. Examples will include a diesel engine, a transmission housing and an engine cover.